2022
DOI: 10.1126/sciadv.abj2479
|View full text |Cite
|
Sign up to set email alerts
|

Surface parameters and bedrock properties covary across a mountainous watershed: Insights from machine learning and geophysics

Abstract: Bedrock property quantification is critical for predicting the hydrological response of watersheds to climate disturbances. Estimating bedrock hydraulic properties over watershed scales is inherently difficult, particularly in fracture-dominated regions. Our analysis tests the covariability of above- and belowground features on a watershed scale, by linking borehole geophysical data, near-surface geophysics, and remote sensing data. We use machine learning to quantify the relationships between bedrock geophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…The lithology of the main stem East River Watershed is dominated by Cretaceous Mancos shale bedrock with Oligocene quartz monzonite and granodiorite laccoliths comprising many of the higher elevation peaks. At Coal Creek, the underlying bedrock is mainly composed of Cretaceous and Eocene sandstones, mudstones, and quartz monzonite and granodiorite intrusive rocks (Gaskill et al., 1991; Uhlemann et al., 2022). The climate in the region is defined as continental subarctic with long, cold winters and short, cool summers (Dfc, according to Koeppen‐Geiger, Peel et al., 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The lithology of the main stem East River Watershed is dominated by Cretaceous Mancos shale bedrock with Oligocene quartz monzonite and granodiorite laccoliths comprising many of the higher elevation peaks. At Coal Creek, the underlying bedrock is mainly composed of Cretaceous and Eocene sandstones, mudstones, and quartz monzonite and granodiorite intrusive rocks (Gaskill et al., 1991; Uhlemann et al., 2022). The climate in the region is defined as continental subarctic with long, cold winters and short, cool summers (Dfc, according to Koeppen‐Geiger, Peel et al., 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The lithology of the main stem East River Watershed is dominated by Cretaceous Mancos shale bedrock with Oligocene quartz monzonite and granodiorite laccoliths comprising many of the higher elevation peaks. At Coal Creek, the underlying bedrock is mainly composed of Cretaceous and Eocene sandstones, mudstones, and quartz monzonite and granodiorite intrusive rocks (Gaskill et al, 1991;Uhlemann et al, 2022).…”
Section: Study Sites and Datamentioning
confidence: 99%
“…Previous studies within the East River watershed (Hubbard et al., 2018), which is representative of many headwater catchments of the Rocky Mountains, have shown that watershed functioning is controlled by hillslope‐scale processes that are expressed in terms of their vegetation cover, and their geomorphological and subsurface characteristics (Wainwright et al., 2022). Large‐scale fracture zones have been identified that are expected to pose a strong control on the watersheds hydrological response (Miltenberger et al., 2021; Uhlemann et al., 2022). Following a system‐of‐systems approach and going to smaller granularity, here we focus on hillslope‐scale hydrological processes, with a particular emphasis on the differences induced by varying bedrock type and vegetation cover.…”
Section: Introductionmentioning
confidence: 99%
“…The shown size of the tree indicates their maximum canopy height. Borehole logs are shown on the right, showing fluid electrical conductivity (blue) and temperature (black) (b), nuclear magnetic resonance (NMR) derived hydraulic conductivity (K est ) (c), and NMR derived water content (d).Note that the K est was calibrated using pumping tests from nearby boreholes(Uhlemann et al, 2022).…”
mentioning
confidence: 99%